THE INFLUENCE OF EMPLOYEE PERFORMANCE ON SERVICE QUALITY AT THE 20 ILIR D2 DISTRICT OFFICE KEMUNING DISTRICT, PALEMBANG CITY - Nyimas Artina (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
Government must be effective and innovative in improving service quality to eliminate the perception of an unfriendly bureaucracy. The purpose of this research is to describe how much influence the performance of public service employees has on community satisfaction at the 20 Ilur D2 Subdistrict office, Kemuning District, Palembang. The sample size was 100 community respondents who used public services at the 20 Ilur D2 Subdistrict office, Kemuning District, Palembang. This research uses a survey as the main research design, which is a type of quantitative research and documentation at the research site. The technique used is Simple Regression Analysis which uses the Partial t-test. The conclusion of the test level (5%) is sufficient evidence that employee performance (X) influences service quality (Y) and then the results of a simple regression analysis show that the employee performance regression is work quality of 0.225, communication of 0.144 and speed of 0.220, the better the results. service quality is also high. In order to improve the quality of service in administering services, facilities and infrastructure must be improved so that the quality of service is a symbol of success through the provision of public services.